Ответ:
Пошаговое объяснение:
1)
4x - 24 = x - 9
4x - x = 24 - 9
3x = 15
x = 15 : 3
x = 5
2)
6 - 3x - 3 = 7 - x
3 - 3x = 7 - x
-3x + x = 7 - 3
-2x = 4
x = 4 : (-2)
x = -2
3)
8x + 3 - 10x - 6 = 9
-2x - 3 = 9
-2x = 9 + 3
-2x = 12
x = 12 : (-2)
x = -6
4)
14x - 14 = 14x - 21 + 7
14x - 14 = 14x - 14
14x - 14x = -14 + 14
0 = 0
множество решений (х любое число)
5)
3x - 6 = x + 2
3x - x = 2 + 6
2x = 8
x = 8 : 2
x = 4
6)
5 - 2x + 2 = 4 - x
7 - 2x = 4 - x
-x + 2x = 7 - 4
x = 3
7)
7x + 1 - 9x - 3 = 5
-2x - 2 = 5
-2x = 5 + 2
-2x = 7
x = 7 : (-2)
x = -3,5
8)
3,4 + 2y = 7y - 16,1
7y - 2y = 3,4 + 16,1
5y = 19,5
y = 19,5 : 5
y = 3,9